THEORETICAL ASPECTS OF INVESTIGATION OF THE COLLECTIVE'S SOCIAL POTENTIAL - G. N. Levchenko (Russian Journal of Economics and Law)
The social-economic changes in the Russian state cause the society transformation. The modern sociology tries to report and analyze these changes. One of the acute sociological problems is the study of the social potential, as it is the characteristic of not only existing but also future possibilities of the society development. The changing of the social development orientations, the social progress criteria, the public objectives achievement changes the idea of the social potential significance which is able to ensure this development.